Fragmentation of sociological market in Russia: thoughts and conclusions - Titarenko, Larisa G. (Journal of the Belarusian State University. Sociology, 2019)
On the basis of the analysis of two large sociological events that took place in Russia in the end of 2016 the author reflects on the state of the modern «market» of ideas developed by sociologists belonging to different segments of the multiform sociological field in Russia. The article gives a brief description of the main groups, represented in Russian modern sociology, singled out by the criterion of representation of four types of sociological knowledge according to M. Burawoy’s classification. The main achievements of each selected group are revealed. Fragmentation is presented as an important feature of the current state of this sociological field. The historical roots and the universal nature of the fragmentation of the production of sociological knowledge are shown. Sociology of education is presented as an actual example of the manifestation of fragmentation of sociological knowledge. It is concluded that fragmentation can contribute to the process of integration of Russian sociology into the international sociological community.